Plasmonic nanobump-assembled platform for absorption enhancement of upconversion materials - Jung, Kinam; Kwon, S. Joon; Ko, Hyungduk (AMER INST PHYSICS, 2018)
We numerically investigate a plasmonic nanobump and upconversion (UC) layer incorporated metal-insulator-metal (MIM) platform as a light absorber. The hemispherical nanobump array situated over a substrate can serve as an optical nanoantenna in a broadband wavelength range. By precisely engineering the design and optical parameters of the insulating spacer layer sandwiched by the top nanobumps and back reflecting metal film, we can manipulate the light absorption inside the upconversion layer. The optical near-field distribution of the nanobump-assembled plasmonic platform is studied using the finite-difference time-domain (FDTD) method to probe the origin of enhanced absorption within the thin UC layer. A suggested mathematical model considering plasmonic and quenching effects of the MIM configuration to analyze the near-field maximum as a function of an insulator thickness is in good agreement with the FDTD result. The 30-fold enhanced light absorption within the UC layer is observed for the MIM plasmonic platform compared to the reference sample. Well-established optical field confinement at the nanoscale gap and excitation of surface plasmons near the nanobumps can be attributed to increased light absorption inside the plasmonic MIM platform. The plasmonic nanobump array platform can be an alternative strategy to apply a highly efficient light absorber to an UC device. Published by AIP Publishing.
Keywords: LIGHT ABSORBER; WAVE-GUIDES; LUMINESCENCE; NANOPARTICLES; SPECTROSCOPY; GAP; METAMATERIALS; NANOANTENNAS; ANTENNAS; UNIFORM